Strength of an obliquely convergent plate boundary: lithospheric stress magnitudes and viscosity in New Zealand. Issue 2 (15th November 2018) - Hirschberg, H P; Lamb, S; Savage, M K
Summary: We assess the stress field that drives lithospheric deformation, focusing on the active New Zealand plate-boundary zone between the Australian and Pacific plates. Here there is a rich database for the horizontal velocity field, and also crustal structure used to derive gravitational potential energy (GPE). We solve the stress balance equations, in the context of a thin sheet model of a viscously deforming lithosphere, for characteristic deviatoric stresses and viscosities, defined as the integral of these with depth (divided by the layer thickness), using the stress method of Flesch et al ., where the input parameters are the fields of strain rate and GPE that apply to the sheet. Synthetic tests show that the stress method is able to resolve the stress field even with high (20 per cent) levels of noise in the input strain rates, and the mean stress is a very robust feature of the inversions, regardless of noise levels. We invert for the stress and viscosity fields in New Zealand, calculating the field of GPE from topography/bathymetry and crustal data, and the field of strain rates from either a long-term (multimillennial) velocity field inferred from the rate and pattern of Quaternary faulting or a short-term (decadal) velocity field directly observed with Global Positioning System (GPS) measurements. In addition, we consider the effect of shear stresses on the subducted plate interface along the Hikurangi Margin (5–15 MPa), or regionally. We explore the effect of GPE on the inversion results by calculating these for a range of deforming layers (i.e. thin sheet with 35–150 km thickness), in effect sampling the lithospheric strength in the crust and mantle. The results show that the derived stress magnitudes (square root second invariant of the stress deviator) are in the range 0–35 MPa, with mean values of 13 ± 1 MPa for all models, comparable to typical earthquake stress drops. Gravitationally induced stresses account for approximately half of the full deviatoric stress. Effective characteristic viscosities are 0.5–5 × 10 21 Pa s in the deforming zone, with an approximate inverse relation between strain rate and viscosity, most likely controlled by thermal structure and/or lithology.